PACKAGE POSSIBILITIES "MATEMATICA" WHEN SOLVING DIFFERENTIAL EQUATIONS AND SAME- BREED EQUATIONS, THE VARIABLES OF WHICH ARE SEPARATED - Khonkulov Ulugbek Khursanalievich,; Sharapov Bakhrom Abdusalov ugli, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article presents methodological recommendations on the possibilities of studying differential equations, in particular, the benefits of commuter mathematical systems. In the study of differential equations, the disclosure of certain aspects of the “matematica” package is considered the main problem. Examples are given on the capabilities of the “matematica” package when solving differential equations and same-breed equations, the variables of which are separated.